2012
DOI: 10.1049/iet-cvi.2011.0140
|View full text |Cite
|
Sign up to set email alerts
|

Who is who at different cameras: people re-identification using depth cameras

Abstract: This paper proposes the concept of bodyprints to perform re-identification of people in surveillance videos. Bodyprints are obtained using calibrated depth-color cameras such as kinect. Our results on a database of 40 people show that bodyprints are very robust to changes of pose, point of view and illumination. Potential applications include tracking people with networks of non-overlapping cameras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…In Table 2, we compare the re-identification rates achieved using the latent features with our previous work using explicit features or bodyprints [3]. It can be observed that the use of latent features has significantly improved the performance, which is mainly due to the fact that the latent features have naturally chosen the discriminative features that contain the relevant information.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Table 2, we compare the re-identification rates achieved using the latent features with our previous work using explicit features or bodyprints [3]. It can be observed that the use of latent features has significantly improved the performance, which is mainly due to the fact that the latent features have naturally chosen the discriminative features that contain the relevant information.…”
Section: Resultsmentioning
confidence: 99%
“…The use of RGB-depth cameras has recently been proposed for person re-identification [3]. The use of these sensors eases the tasks of person segmentation and tracking and allows calibrated virtual views of the person to be created.…”
Section: Techniques For Person Re-identificationmentioning
confidence: 99%
See 3 more Smart Citations